Recruiting and Retaining Special Educators in Rural Areas: Strategies from the Field - Judy Smith-Davis (Educational Considerations, 1989)
Rural administrators put a great deal of time and ingenuity into the effort to recruit and retain qualified personnel. Their strategies range lrom "Home Growing" to telethons.